ROHBECK, J. (2023). Moderne Aufklärung. Erkenntnisse für die Krisen der Gegenwart. Berlín: Springer. - Orozco Pérez, Manuel (Daimon Revista Internacional de Filosofia, 2025)
Reseña de ROHBECK, J. (2023). Moderne Aufklärung. Erkenntnisse für die Krisen der Gegenwart. Berlín: Springer.